A Comparative Study of the Effect of Alcoholic Extract of Tur-meric Plant in Inhibiting the Growth of Candida Albicans - M. sultan, Safaa; M.Saady, Ali; E Irzoqy, Maha (International Journal of Engineering and Technology, 2018)
Turmeric is one of the most widely used spices in nature. It contains many health benefits that are countless. Chinese medicine has been used in the preparation of various medicines because it contains curcumin. The inhibitory activity of the turmeric extract for the fungus of Candida bicans, which causes oral salivary disease, was compared with the inhibitory effect of some antibiotics against this fungus In this study, isolating and diagnosing this type of fungal disease was obtained by obtaining an oral smear from children with oral diarrhea. Two methods were used to detect the process of inhibition by the alcohol extract of turmeric I was by the method of propagation and the second was using the ts immersed in the extract of the turmeric plant turmeric for 48 hours. The results and the physiological and biochemical tests of the survey used in the study showed that the isolation is due to the yeast of Candida albicans. It was also found that the extract of alcohol for turmeric plant showed an inhibitory effect of the growth of this type of fungus by increasing concentration in both ways. The concentration of 16 mg / ml was found to inhibit the growth of Candida and then 8 mg / ml and finally 4 mg / m compared to the fungal antagonists Nystatin, fluoconazole and ketoconazole It has been shown that turmeric is very useful in the treatment of bacterial and fungal infections and can be counted as an antibiotic because it contains curcumin.Â Â